The potential size and duration of an epidemic of bovine spongiform encephalopathy in British sheep. - Kao, R; Gravenor, M; Baylis, M; Bostock, C; Chihota, C; Evans, J; Goldmann, W; Smith, A; Mclean, A (2002)
Because there is a theoretical possibility that the British national sheep flock is infected with bovine spongiform encephalopathy (BSE), we examined the extent of a putative epidemic. An age cohort analysis based on numbers of infected cattle, dose responses of cattle and sheep to BSE, levels of exposure to infected feed, and number of BSE-susceptible sheep in the United Kingdom showed that at the putative epidemic peak in 1990, the number of cases of BSE-infected sheep would have ranged from fewer than 10 to about 1500. The model predicts that fewer than 20 clinical cases of BSE in sheep would be expected in 2001 if maternal transmission occurred at a rate of 10%. Although there are large uncertainties in the parameter estimates, all indications are that current prevalence is low; however, a simple model of flock-to-flock BSE transmission shows that horizontal transmission, if it has occurred, could eventually cause a large epidemic.